Liobagrus huaiheensis, a new species of torrent catfish (Teleostei: Siluriformes: Amblycipitidae) from the Huaihe River basin in Central China - Chen, Zhongguang; Wu, Jiayun; Wen, Anxiang (Zootaxa, 2021)
Liobagrus huaiheensis, a new species of catfish, is described from the Shihe River, a tributary of the Huaihe River, in Henan Province, Central China. It shares a serrated posterior edge of the pectoral-fin spine with L. marginatus, L. nigricauda, L. kingi, L. chenghaiensis, L. andersoni, L. mediadiposalis, L. obesus, L. somjinensis, and L. hyeongsanensis, but it is distinguished from these nine species by having combination of the following characters: 2–3 serrations on the posterior edge of the pectoral-fin spine; 15–17 anal-fin rays; an upper jaw longer than lower one; a rounded caudal-fin with 50–55 rays; 35–37 post-Weberian vertebrae; anus close to pelvic-fin insertion and an adipose-fin posteriorly continuous with caudal-fin, with a marked incision at confluence.